2009
DOI: 10.1007/s10346-009-0150-y
|View full text |Cite
|
Sign up to set email alerts
|

Retrogression characteristics of landslides in fine-grained permafrost soils, Mackenzie Valley, Canada

Abstract: Thirteen landslides (retrogressive thaw flows) were investigated to study the behavior of thaw retrogression in permafrost in the Mackenzie Valley, Northwest Territories (NWT), Canada. Those landslides are all in fine-grained ice-rich permafrost soils. Such landslides usually start from small-scale slope failures followed by retrogressive thaw flows when ice-rich permafrost soils are exposed to the atmosphere. The landslides were marked with survey stakes to measure their retreat rates for the thawing season o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 9 publications
1
25
2
Order By: Relevance
“…The growth of thaw slumps is caused by summer ablation of exposed ice-rich permafrost in headwalls (Lewkowicz, 1987;Grom and Pollard, 2008). Net radiation, summer air temperature, wind and headwall height are the main factors that drive the ablation of ground ice and headwall retreat rates (Lewkowicz, 1985(Lewkowicz, , 1987Robinson and Pollard, 1998;Grom and Pollard, 2008;Wang et al, 2009). Based on field measurements and analysis of image pairs acquired at decadal to multi-decadal time intervals, headwall retreat rates vary from a few to tens of meters per year (e.g., Lantuit and Pollard, 2008;Lantz and Kokelj, 2008;Leibman et al, 2008;Lantuit et al, 2012;Swanson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The growth of thaw slumps is caused by summer ablation of exposed ice-rich permafrost in headwalls (Lewkowicz, 1987;Grom and Pollard, 2008). Net radiation, summer air temperature, wind and headwall height are the main factors that drive the ablation of ground ice and headwall retreat rates (Lewkowicz, 1985(Lewkowicz, , 1987Robinson and Pollard, 1998;Grom and Pollard, 2008;Wang et al, 2009). Based on field measurements and analysis of image pairs acquired at decadal to multi-decadal time intervals, headwall retreat rates vary from a few to tens of meters per year (e.g., Lantuit and Pollard, 2008;Lantz and Kokelj, 2008;Leibman et al, 2008;Lantuit et al, 2012;Swanson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of irrigation-triggered landslides were reported by Zhang et al (2009), and the destruction by blasting of statues of Buddha caused cliff instability at Bamiyan, Afganistan (Margottini 2004). There are also other causesthawing in permafrost regions is the cause of landslides in studies by Wang et al (2009) in Canada and Ma et al (2006) in the Qinghai-Tibet plateau. Vilímek et al (2005) reported landslides caused by glacial retreat in Peru, and Breien et al (2008) reported debris flow caused by a glacial lake outburst flood in Norway.…”
Section: Types and Causes Of Landslidesmentioning
confidence: 94%
“…Landslide risk model based on GIS (Lee, 2005;Wang et al, 2009;Mora et al, 1994;Varner, 1984;Griffiths et al, 2008) as well as related investigations (Kumtepe et al, 2011) were used in the work. The assessment and modelling of level of landslide risk and hazard along with the compiling of relevant maps will allow to increase the efficiency of mastering of territory and apply the landscape planning properly.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…The carried out studies regarding the grade of landslide-related risks and hazards reveal that the growth of factors increases the level of accuracy and reliability of results (Lee, 2005;Wang et al, 2009). …”
Section: Introductionmentioning
confidence: 99%